Tetramer Compound of Manganese Ions with Mixed Valence [MnII MnIII MnIV] and Its Spatial, Electronic, Magnetic, and Theoretical Studies - Cándida Pastor-Ramírez (Crystals, 2018)
Using different spectroscopic techniques and computational calculations, we describe the structural and electromagnetic relationship that causes many interesting phenomena within a novel coordination compound with mixed valence manganese (II, III and IV) in its crystal and powder state. The novel compound [MnII MnIII MnIV(HL)2(H2L)2(H2O)4](NO3)2(H2O) 1 was obtained with the Schiff base (E)-2-((2-hydroxybenzylidene)amine)-2-(hydroximethyl)propane-1,3-diol, (H4L), and Mn(NO3)2.4H2O. The coordination reaction was promoted by the deprotonation of the ligand by the soft base triethylamine. The paper’s main contribution is the integration of the experimental and computational studies to explain the interesting magnetic behavior that the mixed valence manganese multimetallic core shows. The results presented herein, which are rarely found for Mn(II), (III) and (IV) complexes, will contribute to the understanding of the magnetic communication generated by the valence electrons and its repercussion in the local geometry and in the overall crystalline structure.